Cultivating Disciplinary Character in Elementary Schools - Sukarto, Sukarto; Fitriana, Maulida Arum (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Cultivating disciplined character in elementary schools. This research aims to determine the process of forming disciplinary character in elementary schools. Data collection in this research was carried out in three ways, namely observation, interviews and documentation. The research subjects were students of SDN 6 Sokong. Data presentation was carried out using qualitative descriptive methods and data analysis using three methods, namely data reduction, data presentation and conclusion drawing. The research results show that the process of forming disciplined character is carried out in the following way;Comply with school rules, Obey existing instructions, Be honest, have good behavior, Complete assignments from the teacher, Don't leave class when studying.present on time, mBy throwing rubbish in its place, children are able to control emotional attitudes, prevent bad behavior, do assignments with focus, be patient, honest, behave well, complete assignments from teachers, and others.